Pengaruh Budaya Organisasi Terhadap Disiplin kerja Karyawan Di PT Gangsar Lumintu Berkah Lestari - Salma Nurmalia; Dedi Mulyadi; Sungkono Sungkono (JURNAL ILMIAH NUSANTARA, 2024)
This research aimssto analyze the influence offorganizational culture on employee work discipline at PT Gangsar Lumintu Berkah Lestari. The research method uses quantitatitve methods with a verification approach through case studies. To be collected through questionnaires and interviews withhemployees at various levels of the company. The results of this study show that there is a significant influence of organizationallculture on the level of employee work discipline. The focus of the research is to understand the relationship between organizationallculture and employee work discipline and the related factors that can influence this relationship. The research implications regarding the importance of companies paying attention to and strengthening organizational culture that can support work discipline among employees in order tooimprove the company's overalllperformance and productivity.